2004
DOI: 10.1592/phco.24.16.1594.50942
|View full text |Cite
|
Sign up to set email alerts
|

High‐Impact Articles Related to the Pharmacotherapeutic Management of Systolic Heart Failure

Abstract: This compilation is part of a series of five articles identifying important literature in cardiovascular pharmacotherapy. This list focuses on pharmacotherapeutic management of acute decompensated and chronic heart failure. Most of the cited works present the results of landmark clinical studies that have shaped the management of patients with left ventricular systolic dysfunction. Limited primary literature is available for some topics; thus, pertinent review articles also are listed. In addition, consensus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We provide an update to the HF bibliography that was published in Pharmacotherapy in 2008, which followed the original bibliography published in Pharmacotherapy in 2004. 3,4 Many of the cited key articles in the current update represent landmark clinical trials and observational studies that have influenced HF management in the decade since the last key article paper was published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We provide an update to the HF bibliography that was published in Pharmacotherapy in 2008, which followed the original bibliography published in Pharmacotherapy in 2004. 3,4 Many of the cited key articles in the current update represent landmark clinical trials and observational studies that have influenced HF management in the decade since the last key article paper was published.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines were first set forth for the management of patients with mechanical circulatory support by the International Society for Heart and Lung Transplantation. These guidelines address 5 main areas: (1) patient selection for permanent pump implantation, (2) mechanisms to optimize patients prior to device implantation, (3) intraoperative and immediate postoperative concerns, (4) postoperative phase through discharge, and (5) long-term patient management. The authors note that since mechanical circulatory support is a new and evolving field, many of the recommendations are supported by level of evidence C or consensus agreement.…”
Section: Introductionmentioning
confidence: 99%
“…For almost a decade now The Cardiology Practice and Research Network of the American College of Clinical Pharmacy has been developing key articles and guidelines documents in major focus areas of cardiology. In 2004–2006 the first five collections of annotative bibliographies were published on the topics of ACS, arrhythmias, hypertension, systolic heart failure, and dyslipidemias . Over the following years a number of additional key article and guideline documents have been published .…”
mentioning
confidence: 99%
“…It represents a continuation and expansion of the article published in Pharmacotherapy in 2004. 1 The list of publications was compiled by a panel of 10 authors and reviewers who identified key articles that have had the most significant impact on our current understanding and management of both acute decompensated heart failure (ADHF), and chronic systolic and preserved systolic heart failure. The list includes primary literature, pertinent review articles, and consensus documents.…”
mentioning
confidence: 99%